2006
DOI: 10.1016/s1028-4559(09)60239-4
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Ovarian Endometrioid Adenocarcinoma and Endocervical Mucinous Adenocarcinoma

Abstract: The coexistence of primary neoplasms in the ovary and cervix is rare. Diagnosis should be based on histologic examination and requires appropriate treatment for both tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…In contrast, approximately 75% of EC cases are detected at early stages due to irregular bleeding (12). These early symptoms of EC occur in 46% of women with SEOCs and lead to an earlier diagnosis (7,16). Similarly, abnormal vaginal bleeding was the most frequent complaint in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…In contrast, approximately 75% of EC cases are detected at early stages due to irregular bleeding (12). These early symptoms of EC occur in 46% of women with SEOCs and lead to an earlier diagnosis (7,16). Similarly, abnormal vaginal bleeding was the most frequent complaint in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…Only one similar case with ovarian cyst-adenocarcinoma and squamous cell carcinoma of cervix has been reported by K.Srivastav and colleagues in 2009 [2]. In 2006, Huang YD and colleagues reported ovarian endometrioid adenocarcinoma and endocervical mucinous adenocarcinoma [9]. Our patient had squamous cell carcinoma of cervix along with high grade ovarian serous cysadenocarcinoma.…”
Section: Discussionsupporting
confidence: 58%
“…In our case, patient had symptoms pertaining to cervical malignancy; whereas ovarian malignancy was diagnosed after investigating the patient. Histologic examination should be done properly as the prognosis depends on the malignancies being metastatic or synchronous ones; the latter group having better prognosis as shown by earlier studies [2,8,9]. Surgical management should be offered in all such cases as it greatly aids in diagnosis and also helps in improving overall survival.…”
Section: Discussionmentioning
confidence: 96%
“…1,4,5 They are typically localised in the uterus and ovaries and are rarely found in the cervix and ovaries or cervix and uterus. 6,7 The phenomenon of more than two simultaneous tumours is extremely rare, although Atasever et al previously described up to 5 simultaneous ovarian cancers in one patient. 8 Studies have shown that approximately 50% of synchronous gynaecological malignancies are tumours of the uterus and ovaries.…”
Section: Discussionmentioning
confidence: 99%